PROBLEMS IN THE FUNCTIONING OF MARINE TRANSPORT OF UKRAINE IN THE WTO - Poznanska, I. V. (Science and Transport Progress, 2007)
In the article the possible consequences of entry are examinedin ВТО for the marine transport of Ukraine, taking into account the today’s state of economy of country and globalization of world economy.